Dynamic Changes in Chemosensory Gene Expression during the Dendrolimus punctatus Mating Process - Zhang, Su-fang; Zhang, Zhen; Kong, Xiang-bo; Wang, Hong-bin; Liu, Fu (Frontiers in Physiology, 2018)
The insect chemosensory system is pivotal for interactions with their environments, and moths have especially sensitive olfaction. Exploration of the connection between the plasticity of olfactory-guided and molecular level pathways in insects is important for understanding the olfactory recognition mechanisms of insects. The pine caterpillar moth, Dendrolimus punctatus Walker, is a dominant conifer defoliator in China, and mating is the priority for adults of this species, during which sex pheromone recognition and oviposition site location are the main activities; these activities are all closely related to chemosensory genes. Thus, we aimed to identify chemosensory related genes and monitor the spectrum of their dynamic expression during the entire mating process in D. punctatus. In this study, we generated transcriptome data from male and female adult D. punctatus specimens at four mating stages: eclosion, calling, copulation, and post-coitum. These data were analyzed using bioinformatics tools to identify the major olfactory-related gene families and determine their expression patterns during mating. Levels of odorant binding proteins (OBPs), chemosensory proteins (CSPs), and odorant receptors (ORs) were closely correlated with mating behavior. Comparison with ORs from other Dendrolimus and Lepidoptera species led to the discovery of a group of ORs specific to Dendrolimus. Furthermore, we identified several genes encoding OBPs and ORs that were upregulated after mating in females; these genes may mediate the location of host plants for oviposition via plant-emitted volatiles. This work will facilitate functional research into D. punctatus chemosensory genes, provide information about the relationship between chemosensory genes and important physiological activities, and promote research into the mechanisms underlying insect olfactory recognition.